Pengukuran Daya Keluaran DSSC Terhadap Ketebalan Titanium Dioksida Berbasis Internet of Things - S, Muhammad Aulia Rahman; Waluyo, Bakti Dwi; Hutahaean, Harvei Desmon (LPPM UNIKA Santo Thomas Medan, 2020)
Topography and geographical conditions in Indonesia are very supportive in the effort to use solar energy as a producer of electrical energy. In this research, Dye Sensitized Solar Cell (DSSC) was fabricated using the doctor blading deposition method for coating TiO2 onto the substrate. The research focused on the effect of varying TiO2 thickness. TiO2 as an electron jumping pathway and binders for dye molecules, dye to absorb photons which will help generate electricity. the iodide / triiodide redox pair as electrolyte, and carbon as the counter electrode on the DSSC. TiO2, organic dyes, electrolytes, and counter electrodes are arranged and combined with a layered structure as a donor-acceptor layer. In testing the output power measurement using the Internet of Things, where testing cells at a thickness of 292 micrometers using a 7 watt LED lamp produces the maximum power reaches 4429.8 x 10-9 W.